MENINGKATKAN KEMAMPUAN MENGENAL LAMBANG BILANGAN MELALUI PERMAINAN ULAR TANGGA DI KELOMPOK B1 TK PEMBINA NEGERI 1 BANGKO KABUPATEN ROKAN HILIR - Nahdah, Nahdah; Zulkifli N, Zulkifli N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research background is still a lot of children aged 5-6 years who have not been able to recognize the emblem of numbers 1-10, children may not be able to call the epitome of numbers 1-10, children are still one of the numbers match the number swith the symbol. To examine the implementation of snakes and ladders game to increase the ability to know the emblem of numbers in B1 group kindergarten children Pembina State 1 Bangko Rokan Hilir, to know how to do the game of snakes and ladders to improve the ability to know the emblem of numbers in Group B1 kindergarten children Pembina State 1 Bangko Rokan Hilir, to determine the height increase children's ability to recognize the emblem of numbers through the game of snakes and ladders on the B1 group kindergarten children Pembina State 1 Bangko Rokan Hilir. This study uses a classroom action research. Based on the results of data processing and observations of the ability to know the emblem of numbers have increased each cycle. on preliminary data prior to action by the average value of 38.33 percent with criteria not yet developed. After taking action on the first cycle values obtained an average of 49.99 percent with the criteria began to grow, the silus II obtained an average value of 74.09 percent with the criteria developed very well, it can be seen that the method of playing snakes and ladders can improve emblem recognize numbers 1-10 on the B1 group kindergarten children Pembina State 1 Bangko Rokan Hilir.Keywords: Recognizethe Emblem Of Numbers, game of snakes